A Pharmaceutical Study of Dadruhara Churna - L. Sreelakshmi; Ch. Sri Durga; K. Satyaprabha (AYUSHDHARA, 2025)
Dadruhara Churna is a herbal formulation mentioned in the classical text called Siddha Bheshaja Manimala. It is a Dadru Hara Lepa, which contains Chakramarda beeja, Amalaki and Jeeraka as its ingredients. This Churna should be mixed with water and applied to the affected area. The preparation of Churna and Lepa is explained in the Sarangadhara Samhita. In the present study, Chakramarda beeja churna, Amalaki churna, and Jeeraka churna were combined using a Khalwa yantra to prepare Dadru Hara Churna. Step-by-step pharmaceutical procedures were carried out following classical references and standard operating procedures (SOPs). Any loss during the process and the total yield were noted. Additionally, the pharmacological actions of Dadru Hara Churna are discussed briefly. Materials: Amalaki, Chakramarda beeja, Jeeraka. Methods: Churna nirmana and Mardana. Results: Dadru Hara Churna was prepared. Conclusion: Churna nirmana plays key role in topical preparations. In this formulation due to fineness of powder Dadru Hara Churna was very effective in Dadru kushta.